2011
DOI: 10.1007/s10143-011-0371-0
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic telovelar approach to the fourth ventricle: anatomic study

Abstract: The telovelar approach allows reliable access to the fourth ventricle and avoids the splitting of the vermis and its associated "posterior vermal split syndrome." Our objective was to describe the endoscopic topographical anatomy of the telovelum approach to the fourth ventricle as accessed by the cerebellomedullary corridor. A series of 20 fresh and fixed injected anatomical specimens were used. The endoscopic equipment consisted of rigid endoscopes with different lens angles, while the extradural step requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…The feasibility of using endoscopy to perform a telovelar approach has been addressed by a report that addresses the endoscopic topographical anatomy of this region. 5 Because prior reports of endoscopic access to the fourth ventricle used the foramen of Magendie to enter that space, telovelar access by endoscopy has (in theory) the double advantage of minimizing tonsillar retraction and associated injury to the dentate nuclei, while also reducing the degree of telovelar opening required for visualization within the ventricle. 5,14 This method has not been used clinically but shows that minimally invasive surgery may become useful in treating tumors of the fourth ventricle.…”
Section: Technical Aspects Of the Telovelar And Transvermian Approachesmentioning
confidence: 99%
“…The feasibility of using endoscopy to perform a telovelar approach has been addressed by a report that addresses the endoscopic topographical anatomy of this region. 5 Because prior reports of endoscopic access to the fourth ventricle used the foramen of Magendie to enter that space, telovelar access by endoscopy has (in theory) the double advantage of minimizing tonsillar retraction and associated injury to the dentate nuclei, while also reducing the degree of telovelar opening required for visualization within the ventricle. 5,14 This method has not been used clinically but shows that minimally invasive surgery may become useful in treating tumors of the fourth ventricle.…”
Section: Technical Aspects Of the Telovelar And Transvermian Approachesmentioning
confidence: 99%
“…However, in 2010, Di Ieva et al (42) reported the use of the VITOM Exoscope; KARL STORZ GmbH & Co., Tuttlingen, Germany) to generate pictures in assisting with the anatomic study of the cerebellar vascularization. Another anatomic study by Di Ieva et al (41) also used the exoscopic system to assist in the telovelar approach to access the fourth ventricle. The exoscope was used in an extradural macroscopic step to achieve greater image quality assisting the endoscopic procedure (41).…”
Section: Exoscopymentioning
confidence: 98%
“…Another anatomic study by Di Ieva et al (41) also used the exoscopic system to assist in the telovelar approach to access the fourth ventricle. The exoscope was used in an extradural macroscopic step to achieve greater image quality assisting the endoscopic procedure (41). With improvements in stereoscopic view and combined with robotic-assisted surgery (50,51), exoscopy has the potential to be widely practiced along with endoscopy in skull base surgery (e.g., exoscopeassisted microneurosurgery) and in the anatomic laboratory for surgical training ( Figure 13) (82).…”
Section: Exoscopymentioning
confidence: 98%
See 1 more Smart Citation
“…Endoscopic telovelar approaches has also been tried in cadaveric models with some success. 3 Newer methods including neuromonitoring has helped in the safe removal of fourth ventricle tumors with minimum morbidity.…”
Section: 16mentioning
confidence: 99%